Interorganizational Collaboration in Transitional Care – A Study of a Post-Discharge Programme for Elderly Patients - Orvik, Arne (Int J Integr Care, 2016)
INTRODUCTION AND AIM: This article reports a study of a post-discharge programme for elderly patients in Norway. It took place in an intermediate ward for transitional care and was based on collaboration between a municipality and a hospital, which was part of a health enterprise. The aim of the study was to analyse the collaboration and its possible effects on the quality of patient care, and the economic efficiency of the project for the organizations involved. METHODOLOGY: A mixed-methods approach, consisting of interviews, questionnaires and analyses of official documents and statistics. RESULTS: The collaboration was working well on the top level of the organizations, but was more problematic on the operative level. However, there were clear signs of improvement. The patients who received transitional care were more satisfied with their stay at the ward than their previous stay at the hospital. They were discharged to their homes more often and perceived to have a higher level of functioning than the hospital patients. Average costs per patient were also lower in the ward than in the hospital departments. CONCLUSION: The collaboration had mainly positive impacts on the quality of patient care and the economic efficiency of elderly care in the municipality. However, the board of the health enterprise decided to close down the intermediate ward.